Cs-131 as an experimental tool for the investigation and quantification of the radiotoxicity of intracellular Auger decays in vitro. (2nd January 2023) - Fredericia, Pil M.; Siragusa, Mattia; Köster, Ulli; Severin, Gregory; Groesser, Torsten; Jensen, Mikael
Abstract: Purpose: In this work, we set out to provide an experimental setup, using Cs-131, with associated dosimetry for studying relative biological effectiveness (RBE) of Auger emitters. Material and methods: Cs-131 decays by 100% electron capture producing K- (9%) and L- (80%) Auger electrons with mean energies of 26 keV and 3.5 keV, respectively, plus ≈ 9.4 very low energy electrons (<0.5 keV) per decay. Cs-131 accumulates in the cells through the Na + /K + -ATPase. By this uptake mechanism and the alkali chemistry of Cs +, we argue for its intracellular homogeneous distribution. Cs-131 was added to the cell culture medium of HeLa and V79 Cells. The bio-kinetics of Cs-131 (uptake, release, intracellular distribution) was examined by measuring its intracellular activity concentration over time. Taking advantage of the 100% confluent cellular monolayer, we developed a new and robust dosimetry that is entrusted to a quantity called S C -value. Results: The S C -values evaluated in the cell nucleus are almost independent of the nuclear size and geometry. We obtained dose-rate controlled RBE-values for intracellular Cs-131 decay. Using the γH2AX assay, the RBE was 1 for HeLa cells. Using the clonogenic cell survival, it was 3.9 for HeLa cells and 3.2 for V79 cells. Conclusion: This experimental setup and dosimetry provides reliable RBE-values for Auger emitters in various cell lines.